(untitled) (Eurasian Journal of Ecology, 2018)
It was studied the content of mineral elements such as magnesium (Mg), iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), as well as cadmium (Cd) in grains of different rice varieties. The objects of research were different varieties of rice (Oryza sativa L.). Bakanassky RM-2000-183 – maturing rice variety, completely adapted to the conditions in the rice-growing Akdalinski irrigation array (Balkhash district of Almaty region, “Birlik” LLP); Marzhan – middle-grade (originator Kazakh Research Institute of Rice, Kyzylorda, were zoned in 1987 for the Kyzylorda region; Violetta – glutinous variety of rice (Rice Research Institute, 2001; Krasnodar, Russia), and Anayt, Fisht – amylose rice varieties of Russian breeding; Barakat – Chinese variety, Chapsari – Korean rice variety with a high content of gluten. The magnesium content was highest in varieties Anayt, Marzhan and Madina. The lowest magnesium content was found in the variety Bakanas. The remaining varieties occupied an intermediate position on magnesium content. Rice varieties on the magnesium content are located in the following order (µg/g): Anayt (1746.0)>Marzhan (1632.0)>Madina (1622.0)>Violetta (1421.0)>Fischt (1344.0)>Barakat (1259.0)>Chapsari (1213.0)>Baқanas (1205.0). Manganese contained in the largest amount in the grain of Chapsarivarieties, the least amount of manganese found in grains of Fisht and Bakanasvarieties. According to the content of manganese in grain varieties were located as follows (g / g): Chapsari (33.9)>Barakat (25.0)>Madina (21.5)>Marjane (20.5)>Anahit (19.8)>Violetta (19.4)>Fischt (16.45)>Baқanas (14.8). The highest iron content found in grains of Bakanas variety. Marzhan, Barakat, Violetta varieties are distinguished by low iron content (10,45-11,5 µg/g). The remaining varieties occupy an intermediate position: Anay variety have the highest concentration of magnesium, in Chapsari variety was detected the highest content of manganese in comparison with other studied varieties. Bakanas cultivar contained the highest amount of iron. Fischt and Barakat varieties have a relatively low number of investigated elements. Key words: rice, cadmium, growth, stability, variety